Contemporary Visions of Heaven and Hell by a Transylvanian Folk Prophet, Founder of the Charismatic Christian Movement The Lights - Csáji, László Koppány (Open theology, 2022)
I conducted anthropological fieldwork (2010-2018) in a charismatic Christian new religious movement the Lights founded by a Transylvanian contemporary folk prophet in 2008. The new religious movement (NRM) has local hubs in North Serbia, Romania, and Hungary. After offering insight into the techniques of how the prophet receives his visions of heaven and hell (as answers to the existential dilemmas of death and the afterlife), I analyse the role and reception of these visionary journeys. I combine interpretive anthropology with the genealogical way of discourse analysis introduced by Michel Foucault. I conceive of complex roles for the narratives about the prophet’s visionary journeys and his theory of reincarnation. These narratives attract people who encounter the prophet and inspire them to participate in the NRM’s religious events. The group wanted to legitimate the prophet with the visions’ moderate style and the relative correspondence with the Bible. Nevertheless, the prophet and the group recognized the divisive nature of these narratives. They found that they could manage their evangelization by creating graduated access to information to avoid preconception judgements. Between 2012 and 2014, the core group of this NRM (lights and the prophet) worked out a multi-level discourse space in the group: a gradation where access to knowledge is based on status. I called this balanced and long-term initiation process the system of threshold narratives.